Ecclesiology - Mansini, Guy (Sacra doctrina series (Washington, D.C.), 2021)
"The first part of the book explains the antecedent probability both of revelation and of God's institution of a church. It is ecclesiology in the mode of fundamental theology. The second part rounds up what Scripture and Tradition teach about the Church under the heads of the People of God, the Temple of the Holy Spirit, the Bride of Christ, and the Body of Christ. The chapters present this thematic material under each head as a unified whole, across the Testaments, with each chapter keyed to one of the "marks" of the Church: the catholicity of the people of God, the apostolicity of the ministers of the messianic temple, the holiness of the Bride of Christ, and the unity of the Body of Christ. This already organizes things in a proto-systematic frame. The third part of the book gives systematic exploration, in reverse order, to the unity of the Church, with attention to non-Catholic ecclesial communities and churches, to the holiness of the Church, objective and subjective, to the apostolicity of the Church and her mediation of revealed truth and grace, and to the catholicity of the Church, with attention to non-Christian religions. The center of the book, on the definition of the Church as the sacrament of communion, renders recent French Dominican ecclesiology in a form more accessible to undergraduates and seminarians, rooting it in the New Testament teachings on communion and mysterion. The book concludes with a strenuous argument for the necessity of the Church and her mission of evangelization. Thus, the trajectory of the book is from the naturally knowable antecedent probability of the Church to its revealed necessity."--